Culture-Based Screening of Aerobic Microbiome in Diabetic Foot Subjects and Developing Non-healing Ulcers - Noor, Saba; Ahmad, Jamal; Parwez, Iqbal; Ozair, Maaz (Frontiers in Microbiology, 2016)
The study was carried on diabetic foot patients to deduce clinical attributes, the occurrence of the range of aerobic microbial flora and to assess their comparative in vitro susceptibility to the customarily used antimicrobials. We also studied the potential risk factors involved in the development of non-healing ulcers. A total of 87 organisms were isolated from 70 specimens, including Escherichia coli (19.5%) among the Gram-negative and Staphylococcus aureus (18.4%) among the Gram-positive as the predominant aerobes explored. Pseudomonas aeruginosa and Escherichia coli were predominant isolates of non-healing ulcers. The antimicrobial sensitivity pattern revealed that vancomycin (100%) and amikacin (90.4%) exhibited highest sensitivity to Gram-positive cocci, while all strains of Pseudomonas aeruginosa were sensitive towards imipenem (100%). The prevalent uncontrolled glycemic status, altered lipid spectra, the existence of neuropathy and peripheral vascular disease, suggested predisposition towards the development of non-healing lesions. The study has underlined the need for continuous surveillance of bacteria and their antimicrobial sensitivity blueprints to provide the basis for empirical therapy and to minimize the risk of complications. Further, stringent clinical evaluation and medical history will help in revealing the risk of developing non-healing status in diabetic foot ulcers.